Differentiation between incomplete Kawasaki disease and secondary hemophagocytic lymphohistiocytosis following Kawasaki disease using N-terminal pro-brain natriuretic peptide - Jung Eun Choi; Yujin Kwak; Jung Won Huh; Eun-Sun Yoo; Kyung-Ha Ryu; Sejung Sohn; Young Mi Hong (Korean Pediatric Society, 2018)
PurposeHemophagocytic lymphohistiocytosis (HLH) is a hyperinflammatory syndrome with many causes, including Kawasaki disease (KD). The purpose of this study was to identify the laboratory tests needed to easily differentiate KD with HLH from incomplete KD alone.MethodsWe performed a retrospective study on patients diagnosed with incomplete KD and incomplete KD with HLH (HLH-KD) between January 2012 and March 2015. We compared 8 secondary HLH patients who were first diagnosed with incomplete KD with all 247 incomplete KD diagnosed patients during the study period. The complete blood count, erythrocyte sedimentation rate, platelet count, and serum total protein, albumin, triglyceride, C-reactive protein, N-terminal pro-brain natriuretic peptide (NT-proBNP), and ferritin levels were compared. Clinical characteristics and echocardiography findings were also compared between the 2 groups.ResultsThe total duration of fever was longer in the HLH-KD group than in the KD group. White blood cell and platelet counts were higher in the KD group. Alanine aminotransferase, ferritin, and coronary artery diameter were increased in the HLH-KD group compared with those in the KD group. The median of NT-proBNP was significantly higher in the HLH-KD group than in the KD group at 889.0 (interquartile range [IQR], 384.5-1792.0) pg/mL vs. 233.0 (IQR, 107.0-544.0) pg/mL.ConclusionThe NT-proBNP level may be helpful in distinguishing incomplete KD from KD with HLH. The NT-proBNP level should be determined in KD patients with prolonged fever, in addition to the white blood cell count, platelet count, and ferritin level, to evaluate secondary HLH.